SEBUAH TINJAUAN PUSTAKA: DIAGNOSIS HINGGA PROGNOSIS ULKUS KORNEA - Anggia Viona Farehan Adam; Marie Yuni Andari (Yayasan Pendidikan Medika Indonesia, 2023)
Corneal ulcer is a pathological condition in the cornea of ​​the eye which is characterized by the presence of suppurative infiltrates with reverberant corneal defects and discontinuity of the corneal tissue from the epithelium to the stroma. Corneal ulcers can be caused by infection and/or non-infection. In general, corneal ulcers can be classified into 2, namely central corneal ulcers and peripheral corneal ulcers. The diagnosis of the disease can be based on the results of the anamnesis, physical examination, and supporting examinations. Management of corneal ulcers is based on the etiology of the disease. If a corneal ulcer is diagnosed early and treated quickly and precisely, it will produce a good prognosis.